1998
DOI: 10.1002/ana.410440510
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxygen radical production in a transgenic mouse model of familial amyotrophic lateral sclerosis

Abstract: Mutations of the SOD1 gene encoding copper/zinc superoxide dismutase (CuZnSOD) cause an inherited form of amyotrophic lateral sclerosis. When expressed in transgenic mice, the same SOD1 mutations cause progressive loss of spinal motor neurons with consequent paralysis and death. In vitro biochemical studies indicate that SOD1 mutations enhance free radical generation by the mutant enzyme. We investigated those findings in vivo by using a novel, brain-permeable spin trap, azulenyl nitrone. Reaction of azulenyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(106 citation statements)
references
References 31 publications
5
100
0
1
Order By: Relevance
“…Both sALS and fALS are clinically indistinguishable and show similar features. The molecular mechanisms responsible for disease pathogenesis and progression are still unknown; however, studies have shown that patients with fALS have mutations in copper/zinc (Cu/Zn) superoxide dismutase (SOD1), a relevant component of the antioxidant defense system (254). More than 100 SOD1 mutations have been identified in fALS patients (13), most of which result from substitution of one single amino acid, such as SOD1 G85R , SOD1 G37R , and SOD1…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Both sALS and fALS are clinically indistinguishable and show similar features. The molecular mechanisms responsible for disease pathogenesis and progression are still unknown; however, studies have shown that patients with fALS have mutations in copper/zinc (Cu/Zn) superoxide dismutase (SOD1), a relevant component of the antioxidant defense system (254). More than 100 SOD1 mutations have been identified in fALS patients (13), most of which result from substitution of one single amino acid, such as SOD1 G85R , SOD1 G37R , and SOD1…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Oxidative stress is described as one of the possible major causes of motoneuronal death in ALS (Liu et al, 1998). To test whether HDACi treatment could be used as a therapeutic approach to prevent MN death in ALS mice, we first used a simplified cellular model, the NSC34 cell line, a hybridoma of spinal cord motoneurons and neuroblastoma (Cashman et al, 1992), in which cell death can be induced by oxidative stress (Cookson et al, 1998).…”
Section: Hdaci Protects From Oxidative Stress-induced Mn Deathmentioning
confidence: 99%
“…A transgenic mouse model carrying the SOD1-G93A transgene was generated. Indeed, the mice developed ALS, exhibiting progressive motor deficits, paralysis, neurodegeneration, along with prominent mitochondrial abnormalities and increased ROS production in the spinal cord and brain [27,28]. Proteomic analysis of tissue samples identified that the SOD1 protein was carbonylated and aggregated in the spinal cord [29].…”
Section: Cell Models Of P53 For Ros Studymentioning
confidence: 99%